2022
DOI: 10.5603/cj.a2020.0069
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the voltage derived left atrial fibrosis in patients with long-standing persistent atrial fibrillation

Abstract: Background Left atrial (LA) arrhythmogenic substrate beyond the pulmonary veins (PV) seems to play a crucial role in the maintenance of atrial fibrillation (AF). The aim of this study was to evaluate the association of selected parameters with the presence and extent of voltage-defined LA fibrosis in patients with long-standing persistent AF (LSPAF) undergoing catheter ablation. Methods One hundred and sixteen consecutive patients underwent high density-high resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Therefore, parameters predicting LVA burden still remain unclear. It was observed that left atrial appendage (LAA) remains intact despite the development of voltage-defined fibrosis in the body of LA [3,4], recently confirmed in LSPAF patients [2]. Hence, we hypothesised that the presence of LVA may influence the mechanical and electrical function of the left and right (RAA) atrial appendage.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore, parameters predicting LVA burden still remain unclear. It was observed that left atrial appendage (LAA) remains intact despite the development of voltage-defined fibrosis in the body of LA [3,4], recently confirmed in LSPAF patients [2]. Hence, we hypothesised that the presence of LVA may influence the mechanical and electrical function of the left and right (RAA) atrial appendage.…”
Section: Introductionmentioning
confidence: 79%
“…Only patients who were able to maintain sinus rhythm following pulmonary vein isolation (PVI) and cardioversion (n = 140) underwent high-density high-resolution LA bipolar voltage mapping [2963(2213-3145) points per map] using the CARTO®3 system. The mapping protocol is described in detail elsewhere [2]. Briefly, this was performed during coronary sinus (CS) pacing with a Pentaray catheter, acquired with a CONFIDENSE™ module (BW).…”
Section: Detection Of Lvamentioning
confidence: 99%
See 2 more Smart Citations
“…Long-lasting episodes of AF (i.e., persistent forms) lead to pathophysiological changes within the atrial musculature, as a result of intensifying fibrosis, structural and electrical remodeling, especially within the posterior wall of the left atrium (LA) [2][3][4][5][6][7][8][9][10]. These changes have an adverse effect on the prognosis of the termination of arrhythmias and the maintenance of sinus rhythm, hence their inhibition may have a decisive impact on the further clinical course [11,12].…”
Section: Introductionmentioning
confidence: 99%